Access to Water Amid Urbanization: Small-Scale Providers in the Water Supply Context of Cebu City, Philippines - Amadora-Nolasco, Fiscalina; Ligaton, Lauren V.; Abrenica, Brenette; Gaid, Boy Riel (Silliman Journal, 2022)
Water supply is a most pressing need for barangays in Cebu City, Philippines, which are unable to obtain water services from the franchised utility. While many of the communities have been absorbing much of the city’s expansion, the water utility has not been able to keep pace with this growth. The situation has prompted local private entrepreneurs to develop and invest in water systems to augment services. This paper presents data obtained from the mapping activities and the survey with closeand open-ended questions. It revolves around two major themes: an inventory of small-scale water providers who offer household connection services within the franchise area of the water utility, and the level of satisfaction of communities served by operators. The crucial importance of local water distributors in addressing the service provision gap is evident. Their presence is highly appreciated despite the relatively higher tariff which comes with the service. This situation has raised the providers’ stature in the neighborhood to something akin to a patron as loyalty blocs are boldly defined in their favor. They established the business to share water resources and fulfill a community need. This study lends a deeper understanding of the current water landscape amidst the rapid urban growth of the city